The Influence of pH on the Nitrogen-doped TiO2 Structure and Its Photocatalytic Activity on Methylene Blue Degradation - Cahyorini Kusumawardani; Kristiyan Handoyo Sugiyarto; Anti Kolonial Prodjosantoso (Universitas Jenderal Soedirman, 2021)
The mesoporous nitrogen-doped titania (N-doped TiO2) has been synthesized through sol-gel method by refluxing the precursor mixture, continued by hydrolysis process, and then followed by annealing in air at the desired temperature. The pH of precursor mixture solution before hydrolysis process has been varied to study their influence on the resulting N-doped TiO2. The resulting material were characterized using X-Ray Diffraction (XRD), N2 Gas Sorption Analyzer (GSA), X-ray Photoelectron Spectroscopy (XPS), Scanning Electron Microscopy (SEM), and UV Vis Spectrophotometer. The XRD analysis result showed that the pH and water content played an important role on the crystal formation of the N-doped TiO2. The result showed that a high acidity condition resulted in a favored tendency of anatase crystalline phase, while lowering acidity leaded to the rutile formation. Porosity analysis showed the significant influence of pH in the synthesis process on the pore characteristic and pore size distribution of the resulting material. The photocatalytic activity was tested on the methylene blue degradation system comparing to pure TiO2 and commercial Degussa P25 and the result showed that the synthesized N-doped TiO2 provided better photocatalytic activities.